2017
DOI: 10.1002/jctb.5340
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and ammonia adsorption of biochar prepared from distillers' grains anaerobic digestion residue with different pyrolysis temperatures

Abstract: BACKGROUND: Increasing attention is being paid to find an alternative way to handle biogas residue from biogas production which is important for sustainable development of biogas project. In this study, biochars from distillers' grains anaerobic digestion residue (BRC) in the pyrolysis temperature range of 300 to 800 ∘ C were prepared. Subsequently, elemental analysis, thermal stability, specific surface area (SSA), scanning electron microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
(123 reference statements)
0
18
0
Order By: Relevance
“…Biochar, pyrogenic black carbon derived from incomplete biomass combustion under anaerobic condition (Zhang and Wang 2016), had various physicochemical properties determined by the feedstock and pyrolysis conditions (Zheng et al 2018). And it was generally characterized by alkaline nature, porous structure, and high hydrophilic characteristic and C/N ratio as well as large specific surface area (Gul et al 2015;Liu et al 2017).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Biochar, pyrogenic black carbon derived from incomplete biomass combustion under anaerobic condition (Zhang and Wang 2016), had various physicochemical properties determined by the feedstock and pyrolysis conditions (Zheng et al 2018). And it was generally characterized by alkaline nature, porous structure, and high hydrophilic characteristic and C/N ratio as well as large specific surface area (Gul et al 2015;Liu et al 2017).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Wang et al [34] investigated the adsorption of NH4 + -N onto progressively oxidized maple wood biochar and found that the maximum adsorption capacity was 10.1 mg/g. Zheng et al [20] prepared biochar from anaerobic digestion residue, with an NH4 + adsorption capacity of 8.37 mg/g. Zhu et al [22] prepared activated carbon from avocado seeds through methanesulfonic acid activation and found that its NH4 + -N adsorption capacity was 5.4 mg/g.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Moreover, NH 4 + adsorption capacities have been reported to be greater in biochars produced at low temperatures between 300 to 400 • C, possibly due to their higher proportion of acid functional groups [16,17] including high pH [18]. However, a study also found biochars with higher NH 4 + adsorption capacities with increasing pyrolysis temperatures [19]. Though, different feedstock materials were used in the preparation of the biochars examined.…”
Section: Of 15mentioning
confidence: 99%
“…These studies have shown that biochar sorption mechanisms still require further investigation and suggest that hydrochars from the hydrothermal carbonisation (HTC) process are likely to possess greater ability for NH 3 /NH 4 + sorption compared to biochars, given their higher proportion of acidic functional groups. On the other hand, the higher surface areas of biochars may compensate for their lower acidic functionalities since some studies have reported that high adsorbent surface areas and pore volumes increase NH 3/ NH 4 + removal efficiencies [10,19,20]. Moreover, the high surface areas of some biochars may provide more sites for the loading of acidic or cationic species which increase the number of Brønsted and Lewis acid sites respectively.…”
Section: Of 15mentioning
confidence: 99%